King Coo - The thing from space - Stower, Adam (David Fickling Books, 2020)
"Welcome back to the utterly incredible world of King Coo! Visual storytelling abounds in this fun-filled and spirited illustrated story, perfect for fans of Liz Pichon and Andy Stanton.SomeTHING REALLY WEIRD is happening at Ben's school: there's slime on the ceiling, a mysterious cheesy smell, and the headmaster isn't wearing any shoes! And... maybe... there are aliens?! Best friends Ben, King Coo, and Herbert the wombat are on a mission to uncover the truth. They're going to need their most ingenious plan yet to save The THING From SPACE"--Publisher's website
Keywords: Pole, Ben / (Fictitious character) / Juvenile fiction; Schoolboys / Juvenile fiction; Human-alien encounters / Juvenile fiction; Écoliers / Romans, nouvelles, etc. pour la jeunesse; Rencontres avec les extraterrestres / Romans, nouvelles, etc. pour la jeunesse; Schoolboys; Human-alien encounters; Adventure stories; Children's stories; Fiction; Juvenile works; Kinderbuch